WALTER KEMPOWSKI'S DAS ECHOLOT. ABGESANG '45 FROM ARCHIVE TO PRINT. (9th September 2013) - Woods, Roger
ABSTRACT: This article analyses Das Echolot. Abgesang '45, the final volume of Walter Kempowski's ten‐volume 'collective diary' of the Second World War, against the background of recent theoretical discussions about the subjective experience of history and the juxtaposition of homogenised and heterogeneous forms of memory. It also goes into Kempowski's archive of autobiographical material, now held at the Akademie der Künste in Berlin, in order to compare the texts published in Abgesang '45 with the versions originally presented to Kempowski. The analysis shows how the material sent to Kempowski is often far from being a collection of original letters, diaries and notes from the last years of the war, as suggested by the subtitle of the Echolot project – 'ein kollektives Tagebuch'. It also shows that while Abgesang '45 does contain internal dialogue that captures some of the heterogeneity that is associated with individual memories, this dialogue ultimately loses out to a collective account of German suffering through Kempowski's method of selecting, adapting and recontextualising the archive material.